Dipolarization-induced energetic electron precipitation during continuously active periods and isolated substorms - Shukhtina, M. A.; Sergeev, V. A.; Rogov, D. D. (Frontiers in Physics, 2022)
Recently we proposed a spatio-temporal model of auroral absorption for isolated substorms based on linear prediction filter (LPF) technique, which describes the precipitation effects as a sum of properly weighted and time-delayed contributions of short dipolarizations/injections inferred from magnetic MPB index. Here we apply a similar approach to a more general and practically important type of continuous activity including substorms clusters, which is accompanied by intense energetic electron precipitation lasting for many hours and may affect ozone concentration and climate. Unexpectedly, in spite of very different geophysical background, the derived precipitation response to unit-scale injection appeared almost identical to that obtained for isolated substorms. Significant part of absorption variance during active non-storm periods turns out to be the result of superposition of previous injections with short memory less than 4 hours. Our results indicate that, while the injection efficiency is roughly the same, large difference in precipitated fluxes and ionospheric response between two different types of activity is mostly provided by a more frequent appearance and increased intensities of dipolarizations/injections during active periods. In both event types dipolarizations are the decisive factor which determines energetic electron precipitation.